Dynamics of a Discharge-Excited XeCl Laser - Lee, Yee Wing (My University, 1983)
The optical output characteristics of a photo-preionized avalanche discharge XeCl exciplex laser are studied experimentally and analytically. Experimental results are presented for the employing a range of He/Xe/HCl mixtures and discharge conditions. An output energy of ~200 mJ, in an almost flat-topped 60-ns duration (FWHM) optical pulse, has been attained. A viable kinetic scheme has been developed for modelling the laser output pulses, and for investigating the dynamical processes in a pulsed discharge.
The B ²∑⁺₁₂→X ²∑⁺₁₂ emission is characterized by means of Franck-Condon calculations using wavefunctions derived from a Rittner-type potential for the excimer B-state, and a new potential-energy function for the ground X-state. This new function reproduces accurately (~±1%) published experimentally-derived data, and demonstrates the "super-harmonicity" of the ground state molecule. The primary exciplex formation channels, deduced from the electronic structure, are the recombination of Xe⁺ and Cl⁻ ions and the "harpooning" processes via the Rydberg molecules Xe(³P₂) Cl(²P₃/₂) and Xe(³P₁) Cl(²P₃/₂). The latter two processes contribute to high optical gain when ion densities are low.
A comprehensive kinetic model is developed on the basis of achieving good agreement between computed and observed optical pulse-shapes, in terms of total energy, peak power, pulse duration, delay time for onset of emission, and rise- and fall-times. The rate coefficients for electron collision processes are calculated using electron-energy distribution functions derived from Monte-Carlo electron transport simulations (electron-electron scattering is included). Calculated intrinsic laser parameters (unsaturated gain, absorption coefficient and saturation irradiance) are in good agreement with values determined from output-power measurements (employing different output couplers and in-cavity attenuators) used together with gain-saturation theory.
Keywords: Physics; Physics